Outcome of Abdominal Wound Closure Following Continuous and Interrupted Suture in Elective Laparotomy (Faridpur Medical College Journal, 2014)
Closure is a crucial factor in laparotomy wound. Fascial layers provide the major tensile strength in wound closure. Poor wound healing and development of wound infection in incisional wounds are the common complications of open abdominal surgery. Continuous fascial closure commonly practiced and the interrupted closures are also practiced by some surgeon with an assumption that it causes less pain and less wound infection. The aim of this study was to determine the rate of postoperative wound infection and severity of wound pain following interrupted and continuous abdominal wound closure. A comparative cross-sectional study was done at the Department of surgery, Sylhet MAG Osmani Medical College Hospital from 1st July 2007 to 30th June 2008. A total 100 patients of clean-contaminated elective laparotomy were selected. The patients were randomly divided into two groups. Every odds number was included in group-I (interrupted suture) and every even number was included in group-II (continuous suture). Total 14% wound infection was detected in interrupted suture group where as wound infection was 18% in continuous suture group of wound closure. Though the wound infection is higher in group-II but the difference of wound infection is not statistically significant between two groups. The wound pain assessed in seven postoperative days was higher in continuous closure group than interrupted group but the difference was not significant. There is no significant difference of wound infection and wound pain between interrupted and continuous suture group in clean-contaminated laparotomy. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20373 Faridpur Med. Coll. J. 2013;8(2): 73-76